2015
DOI: 10.4049/jimmunol.1402090
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood–Derived Virus-Specific Memory Stem T Cells Mature to Functional Effector Memory Subsets with Self-Renewal Potency

Abstract: Memory T cells expressing stem cell–like properties have been described recently. The capacity of self-renewal and differentiation into various memory/effector subsets make them attractive for adoptive T cell therapy to combat severe virus infections and tumors. The very few reports on human memory stem T cells (TSCM) are restricted to analyses on polyclonal T cells, but extensive data on Ag-specific TSCM are missing. This might be due to their very low frequency limiting their enrichment and characterization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…2). This subset is detectable in very low numbers among circulating human PBMCs [34,35]. In addition, an antigen-experienced but CD44 low memory T cell subset has been suggested as the murine homologue of human TSCMs [36,37].…”
Section: 3 Memory T Cell Ontogeny and Stemnessmentioning
confidence: 99%
“…2). This subset is detectable in very low numbers among circulating human PBMCs [34,35]. In addition, an antigen-experienced but CD44 low memory T cell subset has been suggested as the murine homologue of human TSCMs [36,37].…”
Section: 3 Memory T Cell Ontogeny and Stemnessmentioning
confidence: 99%
“…Data regarding the best T-cell subset from which to derive CAR T-cells for infusion are inconclusive and controversial and most patients receive CD4 + and CD8 + T-cells whose subset derivation is unknown (24, 1120). The ultimate objective of T-cell therapy is to transfer a long-lived T-cell population with the capacity to differentiate into potent tumor-specific effectors and to self-renew (8, 24). Short-lived effector T-cells (T EFF ) possess potent effector function in vitro , however, appear less attractive for adoptive immunotherapy because of their limited proliferation and engraftment in vivo (2527).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of the lymph node homing molecules CCR7 and the leucocyte common antigen (CD45) isoforms RA and RO distinguishes memory from naïve T-cells and allows the dissection of the memory/effector T-cell compartment at least into four main subsets (30, 31): Memory stem T-cells (T SCM ), central memory T-cells (T CM ), effector memory (T EM ) and terminally differentiated effector T-cells (T EMRA ) (24, 30, 31). T CM co-express CCR7 and CD45RO, having lost CD45RA during naïve → memory transition (32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petra Reinke also presented on a versatile expansion procedure for HCMV-specific T SCM using a pp65/IE1 overlapping peptide pool in the presence of IL-7 and IL-15. 22 Meanwhile, Ann Leen reported on beneficial effects of infusing T cell batches that recognize 12 immunogenic antigens related to five viruses (Epstein-Barr virus, adenovirus, HCMV, BKPyV and HHV-6) in allogeneic HSCT recipients. 23 Furthermore, she showed that "third party" virus-specific T cells can be infused in HSCT that have previously failed to respond to any conventional anti-viral therapy.…”
Section: Virus-specific T-cell Infusion As a Mainstream Antiviral Appmentioning
confidence: 98%